Inpatient Specialist Palliative Care in Patients With Left Ventricular Assist Devices (LVAD): A Retrospective Case Series - Tenge, Theresa; Santer, David; Schlieper, Daniel; Schallenburger, Manuela; Schwartz, Jacqueline; Meier, Stefan; Akhyari, Payam; Pfister, Otmar; Walter, Silke; Eckstein, Sandra; Eckstein, Friedrich; Siegemund, Martin; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: Repeat hospitalizations, complications and psychosocial burdens are common in patients with left ventricular assist devices (LVAD). Specialist palliative care (sPC) involvement supports patients during decision-making until end-of-life. In the United States, guidelines recommend early specialist palliative care (esPC) involvement prior to implantation. Yet, data about sPC and esPC involvement in Europe are scarce. Methods: This is a retrospective descriptive study of deceased LVAD patients who had received sPC during their LVAD-related admissions to two university hospitals in Duesseldorf, Germany and Basel, Switzerland from 2010 to 2021. The main objectives were to assess: To which extent have LVAD patients received sPC, how early is sPC involved? What are the characteristics of those, how did sPC take place and what are key challenges in end-of-life care? Results: In total, 288 patients were implanted with a LVAD, including 31 who received sPC (11%). Twenty-two deceased LVAD patients (19 male) with sPC were included. Mean patient age at the time of implantation was 67 [range 49-79] years. Thirteen patients (59%) received LVAD as destination therapy, eight patients (36%) were implanted as bridge to transplantation (BTT), and one as an emergency LVAD after cardiogenic shock (5%). None of the eight BTT patients received a heart transplantation before dying. Most (n=13) patients lived with their family and mean Eastern Cooperative Oncology Group (ECOG) performance status was three. Mean time between LVAD implantation and first sPC contact was 1.71 years, with a range of first sPC contact from 49 days prior to implantation to more than six years after. Two patients received esPC before implantation. In Duesseldorf, mean time between first sPC contact and in-hospital death was 10.2 [1-42] days. In Basel, patients died 16 [0.7-44] months after first sPC contact, only one died on the external sPC unit. Based on thorough examination of two case reports, we describe key challenges of sPC in LVAD patients including the necessity for sPC expertise, ethical and communicative issues as well as the available resources in this setting. Conclusions: Despite unequivocal recommendations for sPC in LVAD patients, the integration of sPC for these patients is yet not well established.